Environmental drivers of litter- and soil-dwelling springtail communities across European forests, assessed by morphotaxonomy and soil DNA metabarcoding - Ivano Brunner; Beat Frey; Maria J.I. Briones; Jérome Cortet; Xavier Domene; Juliane Filser; Aline Frossard; Davey L. Jones; Paul Henning Krogh; Juha Mikola; Olaf Schmidt; José Paulo Sousa; et al. (Applied Soil Ecology, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

A whole ecosystem perspective of hypoxia and its drivers in a large temperate freshwater estuary - Shelby Brunner; Brice Grunert; Kim Weckerly; Pat Anderson; J. Val Klump (Limnology and Oceanography, 2026)
Hypoxic conditions have become increasingly common during the summer in the bottom waters of seasonally stratified inland and coastal waters. While ultimately driven by carbon and nutrient loading from the watershed and subsequent excessive algal production, the formation and duration of hypoxia are largely controlled by coupled physical‐biogeochemical processes. In this study of Green Bay, Lake Michigan, δ 2 H and δ 18 O isotopic tracers illustrate the conservative, estuarine‐like mixing pattern that dominates summertime stratification. Cold hypolimnetic waters originating from Lake Michigan in the northern end of the bay slowly propagate southward (~ 1 km per day) into the increasingly shallower southern bay beneath warmer Fox River and lower Green Bay surface waters, generating a highly stratified water column susceptible to the onset and persistence of hypoxia. As waters become shallower, the hypolimnion compresses and the role of benthic respiration increases, oxygen depletion develops more rapidly, and hypoxia becomes most prevalent. Measurements of sediment oxygen demand at 30 stations (mean = 8.2 mmol m −2 d −1 ) and calculations of apparent oxygen utilization rates within stratified bottom waters result in estimates of sediment oxygen consumption accounting for 14–87% of the total oxygen depletion in the hypolimnion from late July through early September. Residence times for dissolved oxygen in the hypoxic zone are on the order of weeks, making Green Bay sensitive to projections of prolonged stratification and potentially exacerbating hypoxia under a warming climate.

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Comparing soil microarthropod communities derived directly from soil DNA metabarcoding with those from morphological assessment in a drought-prone and irrigated pine forest - Jessica Cuartero; Ivano Brunner; Marcus Schaub; Dariusz J. Gwiazdowicz; Piotr Skubała; Jiayi Qin; Paul Henning Krogh; Beat Frey (Applied Soil Ecology, 2025)

Prenatal exposure to phthalates and phthalate replacements in relation to chorionic plate surface vasculature at delivery - Emily S. Barrett; David Skrill; Elaine Zhou; Sally W. Thurston; Theresa Girardi; Jessica Brunner; Hai-Wei Liang; Richard K. Miller; Carolyn M. Salafia; Thomas G. O'Connor; Jennifer J. Adibi (Science of The Total Environment, 2025)

Impact of PM2.5 exposure in old age and its interactive effect with smoking on incidence of diabetes - Anthony Chen; Jiaqian Yin; Ying Ma; Jian Hou; Weiju Zhou; Zhongliang Bai; Xia Qin; Zhi Hu; Yuntao Chen; Eric J. Brunner; Haidong Kan; Ruoling Chen (Science of The Total Environment, 2024)

Short term air pollution exposure during pregnancy and associations with maternal immune markers - C.S. Yount; K. Scheible; S.W. Thurston; X. Qiu; Y. Ge; P.K. Hopke; Y. Lin; R.K. Miller; S.K. Murphy; J. Brunner; E. Barrett; T.G. O'Connor; et al. (Environmental Research, 2024)

Emydomyces testavorans DNA is detected from shell swabs of companion chelonians - Timothy J. Brunner; Amanda D. Wong; Laura Adamovicz; Amber Simmons; Emilie Ospina; Krista A. Keller (Journal of Exotic Pet Medicine, 2024)

Climatic drivers and tree growth in a key production species: The case of Cryptomeria japonica (Thunb. ex L.f.) D.Don in the Azores archipelago - D.C. Pavão; D. Brunner; R. Resendes; J. Jevšenak; L. Borges Silva; L. Silva (Dendrochronologia, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Commercial wind turbines and residential home values: New evidence from the universe of land-based wind projects in the United States - Eric J. Brunner; Ben Hoen; Joe Rand; David Schwegman (Energy Policy, 2024)

Artificial intelligence to improve ischemia prediction in Rubidium Positron Emission Tomography—a validation study - Simon M. Frey; Adam Bakula; Andrew Tsirkin; Vasily Vasilchenko; Peter Ruff; Caroline Oehri; Melissa Fee Amrein; Gabrielle Huré; Klara Rumora; Ibrahim Schäfer; Federico Caobelli; Philip Haaf; et al. (EPMA Journal, 2023)
Background Patients are referred to functional coronary artery disease (CAD) testing based on their pre-test probability (PTP) to search for myocardial ischemia. The recommended prediction tools incorporate three variables (symptoms, age, sex) and are easy to use, but have a limited diagnostic accuracy. Hence, a substantial proportion of non-invasive functional tests reveal no myocardial ischemia, leading to unnecessary radiation exposure and costs. Therefore, preselection of patients before ischemia testing needs to be improved using a more predictive and personalised approach. Aims Using multiple variables (symptoms, vitals, ECG, biomarkers), artificial intelligence–based tools can provide a detailed and individualised profile of each patient. This could improve PTP assessment and provide a more personalised diagnostic approach in the framework of predictive, preventive and personalised medicine (PPPM). Methods Consecutive patients ( n = 2417) referred for Rubidium-82 positron emission tomography were evaluated. PTP was calculated using the ESC 2013/2019 and ACC 2012/2021 guidelines, and a memetic pattern–based algorithm (MPA) was applied incorporating symptoms, vitals, ECG and biomarkers. Five PTP categories from very low to very high PTP were defined (i.e., < 5%, 5–15%, 15–50%, 50–85%, > 85%). Ischemia was defined as summed difference score (SDS) ≥ 2. Results Ischemia was present in 37.1%. The MPA model was most accurate to predict ischemia (AUC: 0.758, p < 0.001 compared to ESC 2013, 0.661; ESC 2019, 0.673; ACC 2012, 0.585; ACC 2021, 0.667). Using the < 5% threshold, the MPA’s sensitivity and negative predictive value to rule out ischemia were 99.1% and 96.4%, respectively. The model allocated patients more evenly across PTP categories, reduced the proportion of patients in the intermediate (15–85%) range by 29% (ACC 2012)–51% (ESC 2019), and was the only tool to correctly predict ischemia prevalence in the very low PTP category. Conclusion The MPA model enhanced ischemia testing according to the PPPM framework: The MPA model improved individual prediction of ischemia significantly and could safely exclude ischemia based on readily available variables without advanced testing (“predictive”). It reduced the proportion of patients in the intermediate PTP range. Therefore, it could be used as a gatekeeper to prevent patients from further unnecessary downstream testing, radiation exposure and costs (“preventive”). Consequently, the MPA model could transform ischemia testing towards a more personalised diagnostic algorithm (“personalised”).

Forestry in the Face of Global Change: Results of a Global Survey of Professionals - Austin Himes; Jürgen Bauhus; Shankar Adhikari; Saroj Kanta Barik; Hugh Brown; Andreas Brunner; Philip J. Burton; Lluís Coll; Anthony W. D’Amato; Jurij Diaci; Yonten Dorji; Ernest G. Foli; et al. (Current Forestry Reports, 2023)
Purpose of Review Forests support most global terrestrial biodiversity and contribute to the livelihood of billions of people, but these and other benefits are in jeopardy due to global change. This leads to questions, such as how to address the challenges of global change in forest management, given the lack of knowledge and deep uncertainty about future developments. In addition, many of the impediments to implement adaptation strategies are unknown. Recent Findings Here, we present an overview of results from a global survey of 754 forestry professionals (370 researchers and educators, 227 practicing foresters, 37 policymakers, 64 administrators, and 56 with other or unspecified roles) from 61 countries across 6 continents who were interested in global change issues. These professionals were asked about their opinion regarding three different adaptation strategies: resist , adapt , and transform . Most respondents agreed that the majority of global change factors will negatively influence the ability of forests to provide desired ecosystem services. Similarly, they agreed about major challenges when implementing adaptation strategies and specifically whether our current knowledge base is sufficient. These concerns were not limited to ecological aspects, but respondents also highlighted the need for a better appreciation of social/political and economic barriers, especially regarding transformation strategies. In addition, the response patterns, including differences due to economic status, highlight the importance of developing and evaluating adaptation strategies in a local social–ecological context. Summary Our study demonstrates a widespread perception on the part of forestry professionals around the world, especially among researchers and practitioners, that many global change factors will affect sustainable forest management negatively, resulting in the need for active silvicultural adaption. The results also suggest potential barriers to different adaptation strategies, particularly a relative lack of information and social acceptance for transform strategies. Further, this study highlights the importance of social and political factors and the need to understand the general public’s values regarding adaptation strategies as well as how the influence of public opinion is perceived by forest managers.

Identification of organic micro-pollutants in surface water using MS-based infrared ion spectroscopy - Kas J. Houthuijs; Marijke Horn; Dennis Vughs; Jonathan Martens; Andrea M. Brunner; Jos Oomens; Giel Berden (Chemosphere, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Soil fauna drives vertical redistribution of soil organic carbon in a long‐term irrigated dry pine forest - Claudia Guidi; Beat Frey; Ivano Brunner; Katrin Meusburger; Michael E. Vogel; Xiaomei Chen; Tobias Stucky; Dariusz J. Gwiazdowicz; Piotr Skubała; Arun K. Bose; Marcus Schaub; Andreas Rigling; et al. (Global Change Biology, 2022)
Summer droughts strongly affect soil organic carbon (SOC) cycling, but net effects on SOC storage are unclear as drought affects both C inputs and outputs from soils. Here, we explored the overlooked role of soil fauna on SOC storage in forests, hypothesizing that soil faunal activity is particularly drought‐sensitive, thereby reducing litter incorporation into the mineral soil and, eventually, long‐term SOC storage. In a drought‐prone pine forest (Switzerland), we performed a large‐scale irrigation experiment for 17 years and assessed its impact on vertical SOC distribution and composition. We also examined litter mass loss of dominant tree species using different mesh‐size litterbags and determined soil fauna abundance and community composition. The 17‐year‐long irrigation resulted in a C loss in the organic layers (−1.0 kg C m −2 ) and a comparable C gain in the mineral soil (+0.8 kg C m −2 ) and thus did not affect total SOC stocks. Irrigation increased the mass loss of Quercus pubescens and Viburnum lantana leaf litter, with greater effect sizes when meso‐ and macrofauna were included (+215%) than when excluded (+44%). The enhanced faunal‐mediated litter mass loss was paralleled by a many‐fold increase in the abundance of meso‐ and macrofauna during irrigation. Moreover, Acari and Collembola community composition shifted, with a higher presence of drought‐sensitive species in irrigated soils. In comparison, microbial SOC mineralization was less sensitive to soil moisture. Our results suggest that the vertical redistribution of SOC with irrigation was mainly driven by faunal‐mediated litter incorporation, together with increased root C inputs. Our study shows that soil fauna is highly sensitive to natural drought, which leads to a reduced C transfer from organic layers to the mineral soil. In the longer term, this potentially affects SOC storage and, therefore, soil fauna plays a key but so far largely overlooked role in shaping SOC responses to drought.

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

An experimental test of how parasites of predators can influence trophic cascades and ecosystem functioning - Jaime M. Anaya‐Rojas; Rebecca J. Best; Franziska S. Brunner; Christophe Eizaguirre; Miguel Costa Leal; Carlos J. Melián; Ole Seehausen; Blake Matthews (Ecology, 2019)
Parasites can shape the structure and function of ecosystems by influencing both the density and traits of their hosts. Such changes in ecosystems are particularly likely when the host is a predator that mediates the dynamics of trophic cascades. Here, we experimentally tested how parasite load of a small predatory fish, the threespine stickleback, can affect the occurrence and strength of trophic cascades and ecosystem functioning. In a factorial mesocosm experiment, we manipulated the density of stickleback (low vs. high), and the level of parasite load (natural vs. reduced). In addition, we used two stickleback populations from different lineages: an eastern European lineage with a more pelagic phenotype (Lake Constance) and a western European lineage with a more benthic phenotype (Lake Geneva). We found that stickleback caused trophic cascades in the pelagic but not the benthic food chain. Evidence for pelagic trophic cascades was stronger in treatments where parasite load of stickleback was reduced with an antihelmintic medication, and where fish originated from Lake Constance (i.e., the more pelagic lineage). A structural equation model revealed that differences in stickleback lineage and parasite load were most likely to impact trophic cascades via changes in the composition, rather than overall biomass, of zooplankton communities. Overall, our results provide experimental evidence that parasites of predators can influence the cascading effects of fish on lower trophic levels with consequences on ecosystem functioning.

Seasonal dynamics and potential drivers of ranavirus epidemics in wood frog populations - Emily M. Hall; C. S. Goldberg; J. L. Brunner; E. J. Crespi (Oecologia, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

An assessment of potential of hybrid poplar for planting in the Virginia Piedmont - Harold E. Burkhart; Amy M. Brunner; Brian J. Stanton; Richard A. Shuren; Ralph L. Amateis; Jerre L. Creighton (New Forests, 2017)

Canine distemper virus in the Serengeti ecosystem: molecular adaptation to different carnivore species - Veljko M. Nikolin; Ximena A. Olarte‐Castillo; Nikolaus Osterrieder; Heribert Hofer; Edward Dubovi; Camila J. Mazzoni; Edgar Brunner; Katja V. Goller; Robert D. Fyumagwa; Patricia D. Moehlman; Dagmar Thierer; Marion L. East (Molecular Ecology, 2017)
Was the 1993/1994 fatal canine distemper virus ( CDV ) epidemic in lions and spotted hyaenas in the Serengeti ecosystem caused by the recent spillover of a virulent domestic dog strain or one well adapted to these noncanids? We examine this question using sequence data from 13 ‘Serengeti’ strains including five complete genomes obtained between 1993 and 2011. Phylogenetic and haplotype network analyses reveal that strains from noncanids during the epidemic were more closely related to each other than to those from domestic or wild canids. All noncanid ‘Serengeti’ strains during the epidemic encoded: (1) one novel substitution G134S in the CDV ‐V protein; and (2) the rare amino acid combination 519I/549H at two sites under positive selection in the region of the CDV ‐H protein that binds to SLAM ( CD 150) host cell receptors. Worldwide, only a few noncanid strains in the America II lineage encode CDV ‐H 519I/549H. All canid ‘Serengeti’ strains during the epidemic coded CDV ‐V 134G, and CDV ‐H 519R/549Y, or 519R/549H. A functional assay of cell entry revealed the highest performance by CDV ‐H proteins encoding 519I/549H in cells expressing lion SLAM receptors, and the highest performance by proteins encoding 519R/549Y, typical of dog strains worldwide, in cells expressing dog SLAM receptors. Our findings are consistent with an epidemic in lions and hyaenas caused by CDV variants better adapted to noncanids than canids, but not with the recent spillover of a dog strain. Our study reveals a greater complexity of CDV molecular epidemiology in multihost environments than previously thought.

Calf muscle perfusion as measured with magnetic resonance imaging to assess peripheral arterial disease - Gerd Brunner; Jean Bismuth; Vijay Nambi; Christie M. Ballantyne; Addison A. Taylor; Alan B. Lumsden; Joel D. Morrisett; Dipan J. Shah (Medical & Biological Engineering & Computing, 2016)

Lack of Galanin 3 Receptor Aggravates Murine Autoimmune Arthritis - Bálint Botz; Ágnes Kemény; Susanne M. Brunner; Felix Sternberg; Janka Csepregi; Attila Mócsai; Erika Pintér; Jason J. McDougall; Barbara Kofler; Zsuzsanna Helyes (Journal of Molecular Neuroscience, 2016)
Neurogenic inflammation mediated by peptidergic sensory nerves has a crucial impact on the pathogenesis of various joint diseases. Galanin is a regulatory sensory neuropeptide, which has been shown to attenuate neurogenic inflammation, modulate neutrophil activation, and be involved in the development of adjuvant arthritis, but our current understanding about its targets and physiological importance is incomplete. Among the receptors of galanin (GAL 1 – 3 ), GAL 3 has been found to be the most abundantly expressed in the vasculature and on the surface of some immune cells. However, since there are minimal in vivo data on the role of GAL 3 in joint diseases, we analyzed its involvement in different inflammatory mechanisms of the K/BxN serum transfer-model of autoimmune arthritis employing GAL 3 gene-deficient mice. After arthritis induction, GAL 3 knockouts demonstrated increased clinical disease severity and earlier hindlimb edema than wild types. Vascular hyperpermeability determined by in vivo fluorescence imaging was also elevated compared to the wild-type controls. However, neutrophil accumulation detected by in vivo luminescence imaging or arthritic mechanical hyperalgesia was not altered by the lack of the GAL 3 receptor. Our findings suggest that GAL 3 has anti-inflammatory properties in joints by inhibiting vascular hyperpermeability and consequent edema formation.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Characterization of the structure, dynamics, and productivity of mixed-species stands: review and perspectives - Miren del Río; Hans Pretzsch; Iciar Alberdi; Kamil Bielak; Felipe Bravo; Andreas Brunner; Sonia Condés; Mark J. Ducey; Teresa Fonseca; Nikolas von Lüpke; Maciej Pach; Sanja Peric; et al. (European Journal of Forest Research, 2016)

Experimental influence of pH on the early life-stages of sea urchins II: increasing parental exposure times gives rise to different responses - Coleen C. Suckling; Melody S. Clark; Christine Beveridge; Lars Brunner; Adam D. Hughes; Elizabeth M. Harper; Elizabeth J. Cook; Andrew J. Davies; Lloyd S. Peck (Invertebrate Reproduction & Development, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Isolation and biochemical characterization of underwater adhesives from diatoms - Nicole Poulsen; Nils Kröger; Matthew J. Harrington; Eike Brunner; Silvia Paasch; Matthias T. Buhmann (Biofouling, 2014)

More breast cancer patients prefer BRCA-mutation testing without prior face-to-face genetic counseling - Aisha S. Sie; Wendy A. G. van Zelst-Stams; Liesbeth Spruijt; Arjen R. Mensenkamp; Marjolijn J. L. Ligtenberg; Han G. Brunner; Judith B. Prins; Nicoline Hoogerbrugge (Familial Cancer, 2013)

On the emerging role of rabbit as human disease model and the instrumental role of novel transgenic tools - V. Duranthon; N. Beaujean; M. Brunner; K. E. Odening; A. Navarrete Santos; I. Kacskovics; L. Hiripi; E. J. Weinstein; Z. Bosze (Transgenic Research, 2012)

Psychological distress in newly diagnosed colorectal cancer patients following microsatellite instability testing for Lynch syndrome on the pathologist’s initiative - K. M. Landsbergen; J. B. Prins; H. G. Brunner; P. van Duijvendijk; F. M. Nagengast; J. H. van Krieken; M. Ligtenberg; N. Hoogerbrugge (Familial Cancer, 2012)

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Shortened time interval between colorectal cancer diagnosis and risk testing for hereditary colorectal cancer is not related to higher psychological distress - K. M. Landsbergen; J. B. Prins; H. G. Brunner; N. Hoogerbrugge (Familial Cancer, 2011)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Female BRCA mutation carriers with a preference for prophylactic mastectomy are more likely to participate an educational-support group and to proceed with the preferred intervention within 2 years - Karin M. Landsbergen; Judith B. Prins; Yvonne J. L. Kamm; Han G. Brunner; Nicoline Hoogerbrugge (Familial Cancer, 2010)

Worker dominance and policing in the ant Temnothorax unifasciatus - E. Brunner; J. Heinze (Insectes Sociaux, 2009)

Strong Attraction of the Parasitoid Cotesia marginiventris Towards Minor Volatile Compounds of Maize - Marco D’Alessandro; Virginie Brunner; Georg von Mérey; Ted C. J. Turlings (Journal of Chemical Ecology, 2009)

Pharmacological manipulations of interval timing using the peak procedure in male C3H mice - Fuat Balci; Elliot A. Ludvig; Jacqueline M. Gibson; Brian D. Allen; Krystal M. Frank; Bryan J. Kapustinski; Thomas E. Fedolak; Daniela Brunner (Psychopharmacology, 2008)

Toward understanding the human dimensions of the rapidly changing arctic system: insights and approaches from five HARC projects - Henry P. Huntington; Lawrence C. Hamilton; Craig Nicolson; Ronald Brunner; Amanda Lynch; Astrid E. J. Ogilvie; Alexey Voinov (Regional Environmental Change, 2007)

Variation in fine root biomass of three European tree species: Beech ( Fagus sylvatica L.), Norway spruce ( Picea abies L. Karst.), and Scots pine ( Pinus sylvestris L.) - L. Finér; H.-S. Helmisaari; K. Lõhmus; H. Majdi; I. Brunner; I. Børja; T. Eldhuset; D. Godbold; T. Grebenc; B. Konôpka; H. Kraigher; M.-R. Möttönen; et al. (Plant Biosystems, 2007)

A substance flow analysis in the southern hemisphere: cadmium in the Australian economy - Suphaphat Kwonpongsagoon; David T. Waite; Stephen J. Moore; Paul H. Brunner (Clean Technologies and Environmental Policy, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A novel locus for autosomal recessive nonsyndromic hearing impairment, DFNB63, maps to chromosome 11q13.2–q13.4 - E. Kalay; R. Caylan; A. F. Kıroglu; T. Yasar; R. W. J. Collin; J. G. A. M. Heister; J. Oostrik; C. W. R. J. Cremers; H. G. Brunner; A. Karaguzel; H. Kremer (Journal of Molecular Medicine, 2007)

How can remote sensing contribute in groundwater modeling? - P. Brunner; H.-J. Hendricks Franssen; L. Kgotlhang; P. Bauer-Gottwein; W. Kinzelbach (Hydrogeology Journal, 2007)

A novel D458V mutation in the SANS PDZ binding motif causes atypical Usher syndrome - E. Kalay; A. P. M. de Brouwer; R. Caylan; S. B. Nabuurs; B. Wollnik; A. Karaguzel; J. G. A. M. Heister; H. Erdol; F. P. M. Cremers; C. W. R. J. Cremers; H. G. Brunner; H. Kremer (Journal of Molecular Medicine, 2005)

Access of HTB, main metabolite of triflusal, to cerebrospinal fluid in healthy volunteers - M. Valle; M. J. Barbanoj; A. Donner; I. Izquierdo; U. Herranz; N. Klein; H. G. Eichler; M. Müller; M. Brunner (European Journal of Clinical Pharmacology, 2005)

Identification and molecular modelling of a mutation in the motor head domain of myosin VIIA in a family with autosomal dominant hearing impairment (DFNA11) - Mirjam W. J. Luijendijk; Erwin van Wijk; Anne M. L. C. Bischoff; Elmar Krieger; Patrick L. M. Huygen; Ronald J. E. Pennings; Han G. Brunner; Cor W. R. J. Cremers; Frans P. M. Cremers; Hannie Kremer (Human Genetics, 2004)

Arsenic exposure in the wine growing industry in ten French departments - J. P. Grillet; A. Adjmian; G. Bernadac; J. Bernon; F. Brunner; R. Garnier (International Archives of Occupational and Environmental Health, 2004)

Wood ash treatment affects seasonal N fluctuations in needles of adult Picea abies trees: a 15 N-tracer study - M. Jggi; R. Siegwolf; M. Genenger; D. Hallenbarter; I. Brunner; J. Fuhrer (Trees, 2004)

Novel types of mutation in the choroideremia (CHM) gene: a full-length L1 insertion and an intronic mutation activating a cryptic exon - José A. J. M. van den Hurk; Dorien J. R. van de Pol; Bernd Wissinger; Marc A. van Driel; Lies H. Hoefsloot; Ilse J. de Wijs; L. Ingeborgh van den Born; John R. Heckenlively; Han G. Brunner; Eberhart Zrenner; Hans-Hilger Ropers; Frans P. M. Cremers (Human Genetics, 2003)

Special Contribution: BOHEMA 2001-2003: Passive Seismic Experiment to Study Lithosphere-Asthenosphere System in the Western Part of the Bohemian Massif - J. Plomerová; U. Achauer; V. Babuška; M. Granet; U. Achauer; V. Babu.Ka; A. Boušková; K. Bräuer; M. Brož; M. Brunner; T. Fischer; S. Funke; et al. (Studia Geophysica et Geodaetica, 2003)

Experimental oral transmission of largemouth bass virus - J E Woodland; C J Brunner; A D Noyes; J M Grizzle (Journal of Fish Diseases, 2002)
Largemouth bass virus (LMBV) is a recently discovered iridovirus that causes a fatal disease of largemouth bass, Micropterus salmoides (Lacepède). Fish can become infected by waterborne LMBV, but oral transmission of this virus has not been demonstrated previously. Largemouth bass were gavaged with guppies, Poecilia reticulata Peters, which had been injected with LMBV, and then sampled periodically during a 7‐week observation period. The dose of LMBV averaged 10 5.6 tissue culture infectious doses – 50% cytopathic endpoint (TCID 50 ) per largemouth bass. Five of 24 largemouth bass exposed to LMBV became infected with the virus, but none of the fish had clinical signs typical of LMBV disease. Virus titres in largemouth bass were highest in swim bladder (10 5.5–9.5 TCID 50 g −1 ) and were 10 5.2 TCID 50 g −1 or lower in cutaneous mucus, head kidney, trunk kidney, spleen, gonad and intestine. These results indicate that LMBV can be transmitted orally to largemouth bass, but further study is needed to determine the factors affecting pathogenicity of the virus.

Mutations in PATCHED-1, the receptor for SONIC HEDGEHOG, are associated with holoprosencephaly - Jeffrey E. Ming; Michelle E. Kaupas; Erich Roessler; Han G. Brunner; Mahin Golabi; Mustafa Tekin; Robert F. Stratton; Eva Sujansky; Sherri J. Bale; Maximilian Muenke (Human Genetics, 2002)

Bioavailability of repeated oral administration of MDL 100,240, a dual inhibitor of angiotensin-converting enzyme and neutral endopeptidase in healthy volunteers - P. Rousso; T. Buclin; J. Nussberger; F. Brunner-Ferber; H. R. Brunner; J. Biollaz (European Journal of Clinical Pharmacology, 2000)

Pharmacokinetic and pharmacodynamic effects of YM087, a combined V 1 /V 2 vasopressin receptor antagonist in normal subjects - M. Burnier; A. F. Fricker; D. Hayoz; J. Nussberger; H. R. Brunner (European Journal of Clinical Pharmacology, 1999)

Refined mapping of the gene for autosomal dominant retinitis pigmentosa (RP17) on chromosome 17q22 - A. I. den Hollander; S. D. van der Velde-Visser; Alfred J. L. G. Pinckers; Carel B. Hoyng; Han G. Brunner; Frans P. M. Cremers (Human Genetics, 1999)

Rickettsial Relative Associated with Papaya Bunchy Top Disease - Michael J. Davis; Zhentu Ying; Bryan R. Brunner; Alberto Pantoja; Feiko H. Ferwerda (Current Microbiology, 1998)

Differences in Lipoprotein Lipid Concentration and Composition Modify the Plasma Distribution of Cyclosporine - Kishor M. Wasan; P. Haydn Pritchard; Manisha Ramaswamy; Wesley Wong; Elizabeth M. Donnachie; Lane J. Brunner (Pharmaceutical Research, 1997)

Parasitism of the apple maggot,Rhagoletis pomonella, infesting hawthorns in Washington - L. J. Gut; J. F. Brunner (BioControl, 1994)

Restriction site variation, length polymorphism and changes in gene order in the mitochondrial DNA of the yeast Kluyveromyces lactics - Coria O. Roberto; Eugenia Zalce O. María; Mendoza R. Valentín; Alvarez J. Gloria; Cobos de Alba Tuena; Brunner L. Aurora (Antonie van Leeuwenhoek, 1990)

A developmental toxicity and psychotoxicity evaluation of FD and C Red Dye #3 (erythrosine) in rats - Charles V. Vorhees; Richard E. Butcher; Robert L. Brunner; Virginia Wootten; Thomas J. Sobotka (Archives of Toxicology, 1983)